Flora of downstream between the rivers Dniester and Tiligul (Odessa region, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
On the basis of long-term researches, the modern state of flora of the lower reaches of Dniester–Tiligul. The 862 species of higher vascular plants sprout here, with prevalation of hemikryptophytes (51,6 %). Most species are the representatives of ruderal (24,0 %) and steppe (21,4 %) florocoenotyps. In the ecological relation kseromesophytes (34,7 %) and heliophytes (72,0 %) predominate. The synanthropic plants are 51,0 % of species. 93,1 % of invasion species of North Prychornomoria are represented on the territory. Habitation is marked by 66 rare species of plants. It is set that local flora of valleys of estuaries is represented by a large systematic variety, than flora of valleys of small rivers. Participation of hemikryptophytes in most local floras is a little higher than in the explored flora. The grade of prevailing florocoenotypes, and also ecological groups, for most local floras, is saved. It is exposed, that valleys of estuaries are less synantropizated, than flora of small rivers. Location of the most rare species are situated on territories of regional ecological network.
Keywords: lower rivers of Dniester–Tiligul, flora, vascular plants, analysis, sinantropization, conservation.